Evidence for distinct isotopic compositions of sap and tissue water in tree stems: consequences for plant water source identification. Issue 3 (3rd December 2021) - Barbeta, Adrià; Burlett, Régis; Martín‐Gómez, Paula; Fréjaville, Bastien; Devert, Nicolas; Wingate, Lisa; Domec, Jean‐Christophe; Ogée, Jérôme
Summary: The long‐standing hypothesis that the isotopic composition of plant stem water reflects that of source water is being challenged by studies reporting bulk water from woody stems with an isotopic composition that cannot be attributed to any potential water source. The mechanism behind such source–stem water isotopic offsets is still poorly understood. Using a novel technique to extract selectively sap water from xylem conduits, we show that, in cut stems and potted plants, the isotopic composition of sap water reflects that of irrigation water, demonstrating unambiguously that no isotopic fractionation occurs during root water uptake or sap water extraction. By contrast, water in nonconductive xylem tissues is always depleted in deuterium compared with sap water, irrespective of wood anatomy. Previous studies have shown that isotopic heterogeneity also exists in soils at the pore scale in which water adsorbed onto soil particles is more depleted in deuterium than unbound water. Data collected at a riparian forest indicated that sap water matches best unbound soil water from depth below −70 cm, while bulk stem and soil water differ markedly. We conclude that source–stem isotopic offsets can be explained by micrometre‐scale heterogeneity in the isotope ratios of water within woody stems and soil micro‐pores.